ISOLASI & IDENTIFIKASI ALFA SELULOSA DARI KULIT BUAH LIMPASU (BACCAUREA LANCEOLATA) SEBAGAI ALTERNATIF BAHAN BAKU PEMBUATAN MIKROKRISTALIN SELULOSA DARI BAHAN ALAM - Muhammad Muhammad; Rahmalisa Hafifah; Siti Mursyidah; Soraya Aldeina; Yuspa Yuspa; Yulianita Pratiwi Indah Lestari (Bajang Institute, 2023)
The diversity of natural resources in Indonesia, which is very abundant, will directly correlate with chemical diversity which has enormous potential for drug development. Indonesia needs to develop the pharmaceutical industry, especially drug raw materials, thereby making drug prices cheaper. The best solution to this problem is to continuously look for alternatives from Indonesian natural materials, so that the manufacturing process can be carried out both on a laboratory and industrial scale. There are many fruits typical of South Kalimantan and not available in other areas, one of which is Limpasu. This research aims to determine the cellulose content in Limpasu (Baccaurea lanceolata) fruit peel waste using the chemical delignification method. Proving the use of this plant is very important, so that the residue resulting from extraction from the Limpasu fructus cortex can be utilized into a very useful preparation. The research was carried out by first extracting simplicia from the plant, then the remaining residue from the extraction was continued to the alpha cellulose isolation stage. Based on the results of research that has been carried out, it was found that the pure cellulose content in the form of alpha cellulose contained in the Limpasu fructus cortex is 21.08%. These results prove that Limpasu fruit peel has the potential to be used as a source of natural raw materials for the manufacture of other cellulose derivative products that can be used in pharmaceutical formulations.